Effects of volcanic ash on assemblage patterns and biological traits of Chironomidae in a north Andean Patagonian stream, Argentina - Mauad, Melina (2017)
The Puyehue-Cordón Caulle Volcanic Complex eruption occurred on June 4, 2011 (2236 m a.s.l. 40°32'S, 72°7'W). As a consequence, wide areas of Argentina were covered by volcanic ash. In order to investigate the effects of ashfall on chironomid assemblages, we conducted a study at Ñireco River in the southwestern part of the Natural Reserve of Nahuel Huapi National Park that crosses the city of San Carlos de Bariloche, Río Negro, Argentina. We assessed changes in chironomid assemblage attributes and 18 biological traits, by comparing pre-eruption data (December 2009 and December 2010) with post-eruption data (November 2011). Volcanic ash caused negative effects on the chironomid assemblages, where richness and density decreased significantly and the subfamilies Podonominae, Tanypodinae and Chironominae disappeared. The ordination method (principal component analysis) based on abundance of taxa and functional trait composition distinguished pre-eruption from post-eruption periods. Specific tolerance to sedimentation was related to traits mostly associated with predaceous habits such as small size, large head, retractile antennae, long prolegs, presence of ligula and long apical mandibular tooth.